The Integration of Variable Renewable Energy in Present Power System– A Survey - Dr. Jayshiv Uprit (Journal of Power Electronics and Devices, 2019)
This paper spots out the fact that advancement towards research and development is required in present scenario of power system to increase the load demand. To meet the demand involvement of renewable energy is required in today’s energy scheme. This paper indicates the advantages of integrating the variable renewable energy in power system. The integration of VRE will help in maintaining voltage regulation and system stability for present energy generation and distribution technique. The introductory part of paper represents the benefits of integration of variable renewable energy in distributed power system. A review renewable good grid system in recent years indicates the promising potential of such analysis characteristics within the future.